Methane Mitigation Technology In Ruminants To Reduce The Negative Impacts Of Global Warming - Nining Haryuni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2018)
The method used in writing this article is a review of several journals related to methane mitigation technology in ruminants. The purpose of writing this article is to know the technologies that can be applied to the field of animal husbandry to reduce the effects of methane produced by ruminants that can cause global warming. Methane is produced mostly from ruminants in feed fermentation process that occurs in the rumen. 80-95% is produced from fermented feed and 5-20% is produced in the colon. Methane emission mitigation measures in ruminant livestock are conducted in several ways including improving feed quality by increasing concentrate composition, adding feed additive to feed and utilization of acetogenic bacteria.